Equity and access to maternal and child health services in Ghana a cross-sectional study - Samuel George Anarwat; Mubarik Salifu; Margaret Atosina Akuriba (BMC, 2021)
Abstract Background Inequities in the distribution of and access to maternal and child health care services is pervasive in Ghana. Understanding the drivers of inequity in maternal and child health (MCH) is important to achieving the universal health coverage component of the Sustainable Development Goals (SDGs) and poverty reduction in developing countries. However, there is increasing disparities in MCH services, especially in rural -urban, and income quintiles. The study aimed to examine the disparities in maternal and child health care services in Ghana for policy intervention. Methods Data for this study was extracted from the nationally representative Ghana Statistical Service (GSS) Multiple Indicator Cluster Survey (MICS) round 4, 2011. Respondents of this survey were women of reproductive age 15-49 years with a sample size of 10,627 households. The models were estimated using multivariate regression analysis together with concentration index (CI) and risk ratio (RR) to assess the distribution of MCH indicator groups across the household wealth index. Results The results show that women with secondary school level and above were more likely to receive family planning, prenatal care, and delivery by a skilled health professional than those without formal education. Mothers with low level of educational attainment were 87% more likely to have their first pregnancy before the age of 20 years, and 78% were more likely to have children with under-five mortality, and 45% more likely to have children who had diarrhoea. teenage pregnancy (CI = − 0.133, RR =0.679), prenatal care by skilled health worker (CI = − 0.124, RR =0.713) under five mortality, child underweight, reported diarrhoea, and suspected pneumonia, though not statistically significant, were more concentrated in the poorer than in the richer households, The RR between the top and bottom quintiles ranged from 0.77 for child underweight to 0.82 for child wasting. Conclusion Geographic location, income status and formal education are key drivers of maternal and child health inequities in Ghana. Government can partner the private sector to implement health policies to address inequalities in MCH services through primary health care, and resource allocation skewed towards rural areas and the lower wealth quintile to bridge the inequality gaps and improve MCH outcomes. The government and the private sectors should prioritize female education, as that can improve maternal and child health.